Hidden in plain sight : - Joachimsthaler, Erich (Harvard Business School Press, 2007)
Introduces innovation and growth model that shows you how to become an unbiased observer of people's consumption and usage behaviors. This book helps companies generate organic growth through products, services, solutions, and experiences that enhance peoples' lives. It also offers you an approach to executing your company's growth strategy.